Sequence of the cellulase gene of Clostridium thermocellum coding for endoglucanase B. - Grépinet, O (1986)
The nucleotide sequence of the CelB gene, encoding the extracellular endoglucanase B of Clostridium thermocellum, is reported. The putative start of the 1689 bp coding sequence was assigned to an ATG codon which is preceded by an AGGAGG sequence typical of ribosomal binding sites in Gram-positive bacteria. The amino-terminal end of the deduced protein sequence is similar to signal peptides described for other bacterial secretory proteins. The carboxy-terminal ends of endoglucanases A and B appear to be remarkably homologous. A striking feature of the conserved region is that both proteins contain two reiterated stretches of 23 aminoacids each, separated by 9 residues.